Primary Ewing’s sarcoma of the kidney: A diagnostic and therapeutic challenge - Chatterjee, Souvik; Kumar, Kundan; Mondal, Soumya; Maiti, Krishnendu; Pal, Dilip Kumar (Indian Journal of Case Reports, 2020)
Ewing’s sarcoma is a highly malignant tumor that usually arises from the bone and soft tissue of the extremity. Primary Ewing’s sarcoma of the kidney is extremely rare. Here, we present the case of primary Ewing’s sarcoma of the kidney in a 30-year-old man, presented with the left flank pain, and treated with the left radical nephrectomy with adjuvant chemotherapy. Despite the treatment options, the overall survival of the disease is poor. The relevant literature of this rare entity was reviewed.